Impact of Regulating Non-Regular Employment on Firms' Employment Decisions - Wooram Park; Yoonsoo Park (Korea Development Institute (KDI), 2018)
- Regulations on the use of non-regular workers can encourage the conversion to regular workers and reduce firms' labor use. They can also increase the use of non-regular employment types that are not subject to the law. - An analysis on the impact of the non-regular employment protection law (2007) on firms' employment decisions found that regular employment increased and non-regular employment (fixed-term/agency workers who fall within the scope of the law) decreased. - However, total employment, including non-regular workers, dropped slightly and the use of nonregular workers (contract workers etc.) not subject to the law increased. - The impact of regulating the use of non-regular workers on firms' employment decisions can vary depending on the degree of rigidity in working conditions for regular employees. - Analysis on the effect of the non-regular employment protection law by firm characteristics showed that conversion to regular status was lower and the use of non-regular workers not subject to the law was higher among firms who believed that the working conditions for regular employees were highly rigid. - To fulfill the intended goals of the law, measures to ease the rigidity of working conditions for regular employees must be sought. - The conventional concept of labor flexibility needs to be extended to cover working conditions (wage, working hours) to evenly promote workers' demand for job security and employers' need for flexible labor management.
Keywords: 330